Pengembangan dan Pemberdayaan Potensi Desa Sabdodadi Kapanewon Bantul Kabupaten Bantul Daerah Istimewa Yogyakarta - Purnomo, Prasetyo Sidi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Abstract— Through the Research and Community Service Institute (LPPM), Atma Jaya University Yogyakarta carries out the Community Service 5.0 program which focuses on community service programs through courageous means without direct contact with local residents, with a bold overall mechanism process, starting from taking, program, to implementation of the work program. The KKN 49 group was located in Sabdodadi Village, Kapanewon Bantul, Bantul Regency, Sepecial Region of Yogyakarta. Sabdodadi village has several potentials, such as cultural potential, tourism potential, and natural resource potential (SDA). Based on the potential of existing natural resources, the KKN 49 group will make village potentials regarding